The cultivation of university students’ spiritual wellbeing in holistic education: longitudinal mixed-methods study - Pong, Hok-Ko (International journal of children's spirituality, 2021)
This longitudinal mixed-methods study, which consisted of (1) questionnaire surveys and (2) individual in-depth interviews, explored the development of the spiritual wellbeing of university students over the past four years under the cultivation of holistic education. A sample of 276 in quantitative and 32 students in qualitative studies was successfully followed up. The quantitative results suggest a main effect of time on the spiritual wellbeing of students, though no significant interaction effect is found between time and other variables, including gender, age and major disciplines. Qualitative results further show that holistic education through experiential learning contributes highly to the development of Chinese university students’ spiritual wellbeing in three specific domains, namely personal and communal, environmental and transcendental. The finding indicates that (1) environment-related forces and (2) education-related dynamics were critical factors for the successful implementation of holistic education through experiential learning in universities.